PENGARUH VARIASI DOSIS VAKSINASI ANTRAKS TERHADAP TITER ANTIBODI DAN TOTAL PROTEIN PLASMA PADA TERNAK DOMBA LOKAL - Paulina Jolanda Naif; Maxs U. E. Sanam; Elisabet Tangkonda (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2020)
Anthrax is an acute infectious disease caused by the bacterium Bacilus anthracis. This disease can attack domestic and wild animals, especially herbivorous animals, such as cattle, sheep, goats, sheep and can also attack humans. One of the preventive measures that can be taken is vaccination. In general, anthrax vaccination in livestock in Indonesia uses live spore vaccines, which contain B. anthracis 34F2 strain which is toxic, and is not encapsulated. Anthrax vaccination in goats and sheep can cause anaphylactic shock effects because it can still produce toxins. The incidence of anaphylactic shock in goats and sheep can be prevented by modifying the vaccination dose, namely the preinoculation dose. This study was conducted to determine whether there was a difference in the antibody titer value and the total plasma protein of sheep who received variations in the vaccination dose. There were 12 sheep that were divided into three groups, namely the control group, sheep that received the full dose of vaccination (0.5 cc) and sheep that received the preinoculation dose. Measurement of antibody titers was carried out using the indirect ELISA method and measurement of total plasma protein using a refractometer. The results of the analysis of variance (ANOVA) showed that there was no significant difference (P> 0.05) of the variation in the vaccination dose on antibody titer and total plasma protein. In general, the paired t test results did not show any difference in antibody titer values ​​at each sampling time. The antibody titer was negative until the 12th week after vaccination. The highest antibody titer value in the sheep group with the full dose was seen at week 12, while the highest titer in the sheep group with the preinoculated dose was seen at week 10